PENGADILAN AGAMA DAN KEWENANGANNYA - Herdawati; Muannif Ridwan (Indra Institute Research & Publication, 2022)
The religious court is an agency whose task is to determine and carry out activities related to family cases such as cases of divorce, divorce, inheritance and others. Religious courts have the right to give decisions on all kinds of cases related to civil law. Nowadays, since increasing the number of Covid cases in court, many mothers have filed for divorce from their husbands. The main reason is the economic factor where the economy is getting more difficult but many husbands are still relaxed and don't want to work so that women, especially mothers, are doing jobs both looking for sustenance and taking care of the household and children. Therefore, mothers who wish to file for divorce must go to the nearest court office so that the process can be carried out according to the procedures and authorities that have been determined by the local religious court and assisted by the judge as one of the members in charge of determining and deciding cases related to divorce. with this husband and wife.